Ethical Issues of Cyberstalking and Personal Privacy in Pakistan: A Literature Survey - Atiya Sharf; Saeed Akhtar; Swera Sharf; Muhammad Asif (Universitas Pendidikan Indonesia (UPI), 2021)
Electronic media is the fastest-growing technology of the modern era. Our society is relying on technological powers and lighting the fast speed of the internet to get maximum information about everything anywhere in the world. It plays a significant role in providing various facilities to the users but at the same time, personal privacy and cyberstalking issues must face. Cyberstalking is considering a major arising challenge to the modern world currently. Modification of technologies has a direct relationship with increase crimes of cyberstalking. This article represents a glimpse of unexpected activities like ethical dimensions of privacy, cyberstalking, and cyber harassment in Pakistan. Furthermore, the strategies associated with cyberstalking crimes, judicial involvement measures, and preventative proposals are also reported minimizing this emerging global crime.